Pergolakan Andi Azis di Makassar - Bustan Buhari (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2017)
Andi Azis was born in Barru, South Sulawesi 19 September 1924. He had attended Europe Leger School but was not finished. Andi Azis was later taken by a Dutch Resident Assistant Resident to the Netherlands. Andi Aziz by many people is believed to be a member of the military with a good person but in the scale of military unity KNIL in South Sulawesi itself more inclined as a puppet. Colonel Schotborg and Sumokil are the main controllers of KNIL force in Makassar City. When the Andi Aziz rebellion in Makassar, to anticipate the RIS Government in Jakarta has formed a joint forces Expedition East Indonesia. These troops consist of battalions from West Java, Central Java and East Java supported and Police. Commander of the Command appointed Colonel Kawilarang Panglima.